If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 39 = -38 Reorder the terms: 39 + 7x = -38 Solving 39 + 7x = -38 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-39' to each side of the equation. 39 + -39 + 7x = -38 + -39 Combine like terms: 39 + -39 = 0 0 + 7x = -38 + -39 7x = -38 + -39 Combine like terms: -38 + -39 = -77 7x = -77 Divide each side by '7'. x = -11 Simplifying x = -11
| x=(4x)(4x)-25x | | 6(3x-7)-12-4x=9x-(7x+6) | | 6x^2+10x-25=0 | | 25/6+11/2 | | 2(3+2)=5(2y-4) | | -19x^3+37x^2+160x-34=0 | | 4x=6x+13 | | 2/5x+1=-23 | | X=3ln(x) | | 8x-9=24 | | (x^2-4x+5)/(x-2) | | 6y-0.6=7y | | 2(4+2y)+5y=17 | | r-6.5=-6.8 | | y=1.3x-4.7 | | 5-9-8/-9+9 | | 5(4x-7)-4(x+2)-18x= | | 24+3n=3(n+8) | | 2.8(3r+9)-1.5r= | | 3/5(x+4)+1/2x=x+3 | | 4y+4-8y-1= | | 8y-1-4y+4= | | 00.5X+10=-0.05x+70 | | 200x-51=49 | | -4(1+8k)+8k=-24-4k | | (2x+5)-(7x+1)= | | (7x+1)-(2x+5)= | | 7x+1-2x+5= | | 7d=58+9d | | (8x-8)-(6x-10)= | | 4x=-(3/16) | | 4/x+7/x^2-2/x^3 |